Prevalence of Levodopa-Induced Peripheral Neuropathy in Patients with Parkinson’s Disease and Vitamin B12 Deficiency: - Sadat-Ebrahimi, Seyyed-Reza; Yazdchi Marandi, Mohammad; Ayromlou, Hormoz; Pezeshki, Zakaria; Asadi, Rogayye; Najmi, Safa (Galen Medical Journal, 2021)
Background: Parkinson’s disease (PD) is one of the widespread neurodegenerative diseases. Recently, a few studies have suggested that treatment with levodopa and vitamin B12 deficiency may have some role in developing peripheral neuropathy (PN) among PD patients. Hence, the aim of this study was to evaluate PN in patients suffering from PD under long-term treatment with levodopa and also vitamin B12 deficiency in these patients. Materials and Methods: Thirty PD patients who received levodopa for at least two years, 30 levodopa-naïve PD patients, and 30 age-matched controls individuals were included. The participants were subjected to electrodiagnostic tests and the level of vitamin B12 was measured. The prevalence of neuropathy was determined according to electrodiagnostic criteria and compared among the three groups. Results: Overall, 23.3% of cases in levodopa receivers, 3.3% in the levodopa-naïve group, and 3.3% in control group had PN (odds ratio=8.8, 95% confidence interval=1.7-45.6). Levodopa group had significantly lower serum vitamin B12 than the other two groups (P=0.006). Vitamin B12 insufficiency was detected in 36.6% of patients in the levodopa group, which was significantly higher than other groups (23.3% in the levodopa-naïve and 6.6% in the control groups, P=0.02). A significantly negative correlation was noticed between the duration of levodopa exposure and serum level of vitamin B12 (r=-0.31, P=0.016). Conclusion: Our study demonstrated a significantly higher prevalence of vitamin B12 insufficiency and PN in PD patients under treatment with levodopa. Also, our results advocate the role of levodopa in PN development through the vitamin B12 derangement. [GMJ.2021;10:e1837]